Revitalizing dharma and prema as the foundation of a Hindu curriculum of love in confronting the finitude of life - Prasanthy Devi Maheswari; I Ketut Wardana; Ravinder Nath; Ni Luh Ersania (Institute for Advanced Science Social, and Sustainable Future, 2026)
Background: Human life is essentially finite, requiring a philosophical and ethical foundation that can guide humans in facing limitations with meaning and balance. Dharma as the principle of universal truth and Prema as transcendent love are the core of Hindu teachings that can be revitalized as the foundation of a love-based curriculum. This study aims to formulate a conceptual model of a Dharma and Prema-based curriculum that is relevant in facing the finite reality of life. Methods: Using a qualitative approach based on critical literature review, this study examines Hindu sacred texts, educational philosophy literature, and contemporary spirituality theories to construct an integrative theoretical framework. Findings: The findings show that Dharma and Prema, when constructed in a love-based curriculum, are capable of fostering ethical awareness, emotional balance, and strengthening individual spirituality in facing suffering, loss, and the transience of life. This model differs from conventional moral curricula because it integrates the transcendental dimensions of Hinduism with modern educational practices, thereby contributing new insights to the development of a love-based spiritual curriculum. Conclusion: In conclusion, the revitalization of Dharma and Prema as a Hindu love curriculum offers an innovative perspective for facing the limitations of life with full awareness, meaning, and inner peace. Novelty/Originality of this article: The originality of this article lies in the development of the concept of a Hindu love curriculum that emphasizes the synthesis between transcendental values and contemporary pedagogical practices, an aspect that has not been widely explored in the literature on spiritual education.